Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 1 - Limits and Their Properties - 1.5 Exercises - Page 88: 37



Work Step by Step

$\lim\limits_{x\to-3^-}\dfrac{x+3}{x^2+x-6}=\lim\limits_{x\to-3^-}\dfrac{(x+3)}{(x+3)(x-2)}=\lim\limits_{x\to-3^-}\dfrac{1}{x-2}$ $=\dfrac{1}{-3^--2}=-\dfrac{1}{5}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.